Włączenie cyfrowe w prawie Unii Europejskiej .......... 67 (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
SOCIAL INCLUSION IN EUROPEAN UNION LAW The objective of the European Union as set out in Article 3 Section 3, paragraph 2 of the Treaty on European Union is to “combat social exclusion”. One form of this exclusion is digital exclusion, which means a lack of access to or ability to use information and communication technologies. It prevents EU citizens from fully participating in social, economic and cultural life. The article aims to identify solutions in EU law intended to promote digital inclusion in the European Union and thus combat social exclusion in the area of Europe’s digital transformation.